Profile of consumers of pork sold in the municipality of Grajaú, State of Maranhão, Brazil - Silva, Iran Alves da; Rodrigues, José Murilo Sousa; Borges, Jordane de Oliveira (Scientia Agraria Paranaensis, 2017)
<!–[if gte mso 9]> <![endif]–> <span style="font-family: ’Helvetica’,sans-serif; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The objective of this study was to characterize the profile of pork consumers in the municipality of Grajaú Maranhão State, Brazil, where, in the second half of 2014, 200 (two hundred) consumers were interviewed at fairs and supermarkets in that municipality. Questionnaires containing 19 closed questions were used to identify aspects related to socioeconomic profile, consumption habits, factors affecting purchase decision, characteristics and attributes related to consumption. Among the interviewees, 147 (73.5%) said they did not know the nutritional value of pork. With regard to public health, 168 (84%) consumers stated that they did not know about the cycle of teniasis/cysticercosis, and 173 (86.5%) interviewed showed dissatisfaction with the hygienic factors at the time of marketing, and 104 (52%) raised concerns about the imminent risks of zoonoses. It was also observed that there are demands regarding the improvement of the quality of the product offered, among them are: genetic and food breeding, animal welfare practices and improvements in slaughter and processing. The consumption of pork in the municipality in question is still considered relatively low, since only about 21 (10.5%) consumers reported regularly consuming it, a fact that seems to be mainly related to consumers’ misperceptions about the quality of this type of meat, among other factors. <!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>